A computational and experimental comparison on the nucleation of fatigue cracks in statistical volume elements. (August 2020) - Kakandar, Ebiakpo; Barrios, Alejandro; Michler, Johann; Maeder, Xavier; Pierron, Olivier N.; Castelluccio, Gustavo M.
Highlights: Integrating physics-based models for predicting fatigue crack nucleation. Modelling and experiments in small volumes. Validation of crack nucleation orientation and nucleation life statistical distribution. Use of non-local FIPs in microstructure-sensitive models with gradients. Abstract: The failure of micron-scale metallic components presents significant variability as a result of their size being comparable to microstructural length scales. Indeed, these components do not represent the bulk of the material but correspond to statistical volume elements (SVEs). This work investigates the role of SVEs on fatigue crack nucleation with a novel comparison between microbeam experiments and microstructure-sensitive simulations. We recreate multiple microstructural computational realizations to estimate fatigue crack nucleation lives and orientations by means of physics-based crystal plasticity models. We demonstrate a unique approach to validate microstructure sensitive models and quantify the fatigue crack stochasticity associated with small volumes.